The - Stephen Greenblatt; general editor; M.H. Abrams; founding editor (W.W. Norton, 2012)
The Ninth Edition offers more complete works and more teachable groupings than ever before, the apparatus you trust, and a new, free Supplemental Ebook with more than 1,000 additional texts. Read by more than 8 million students, The Norton Anthology of English Literature sets the standard and remains an unmatched value